A low-temperature operated in situ synthesis of TiC-modified carbon nanotubes with enhanced thermal stability and electrochemical properties. Issue 11 (10th May 2022) - Du, Huanhuan; Wang, Yurong; Xiao, Dongyang; Zhang, Yili; Hu, Fangjing; Sun, Leimeng
Abstract : A low-temperature operated in situ synthesis of TiC-modified CNTs is demonstrated to improve the thermal stability and electrochemical properties of CNTs. Abstract : Carbon nanotubes (CNTs) with superior thermal and electrochemical properties are desirable for a large variety of applications. Herein, an in situ synthesis carried out at 1050 °C is proposed for the realization of titanium carbide (TiC) modified CNTs (TiC@CNTs) via a carbothermal treatment of the TiO2 -coated CNTs deposited by a TALD technology, preserving the structural morphologies of CNT samples. Crystalline and amorphous TiC layers/nanoparticles are observed around the walls of CNTs, serving as a thermal insulation layer to enhance the thermal stability of CNTs. The TiC@CNT sample exhibits a minimal mass loss of 3.1%, which is 20.9% and 82.3% for the TiO2 @CNT and pristine-CNT samples, respectively. In addition, the TiC@CNT electrode shows good energy storage performances, with a specific capacitance of 2.83 mF cm −2 at 20 μA cm −2, which is about 3.5 times higher than that of the pristine-CNT electrode, showing the potential of TiC@CNTs as next-generation electrode materials.